EFFICIENT USE OF CLEAN WATER AT ALILA VILLAS ULUWATU, BALI - Marbun, Fanny Elizabeth; Raka Dalem, Anak Agung Gde; Muksin, I Ketut (SIMBIOSIS, 2022)
Human beings depend on water not only to fulfill domestic needs but also to fulfill production, industry and other needs. Because of high quality of water is needed for the hotel industries, it is necessary to conduct observations to find out efficiency use of clean water in hotels or villas. Alila Villas Uluwatu Bali is one of the luxurious five-star  villas  which has various facilities and infrastucture that are provided so that the use of clean water is certainly quite a lot. This research is carried out  with purpose to know efficiency effort of using clean water at Alila Villas Uluwatu Bali. The methods used in this study are interview, document examination and field observation. The data obtained is analyzed qualitatively. Based on the result of this study, the average clean water consumption of Alila Villas Uluwatu in 2017 was 2.80 liters/visitor and in 2018 it was 2.73 liters/visitor. In 2018 the efficiency of clean water use at Alila Villas Uluwatu was 2.5% compared to 2017. Other efforts that can be made to minimize clean water consumption at AVU are by using water fixtures and sanitary, absorbing water through biopori and infiltration wells on green land, optimizing water pipes, limiting shower flow and controlling leaks and regulating water pressure periodically. The meaning of the results of this study is that Alila Villas Uluwatu has reduced waste that is not good for the environment, but Alila Villas Uluwatu reprocesses it for hotel operations.